Metallic cobalt to spinel Co3O4-electronic structure evolution by near-ambient pressure photoelectron spectroscopy - Reddy, Kasala Prabhakar; Jain, Ruchi; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2017)
In the present study, valence band (VB) and core level photoelectron spectroscopy was carried out to investigate the electronic structural changes from polycrystalline Co to spinel Co3O4, via CoO at near ambient pressures (NAP; similar to 0.1). O-2 Co and H-2-CoOx gas solid oxidative and reductive interactions, respectively, have been explored with UV photons (He I) or low kinetic energy electrons (<= 16 eV) under NAP conditions. Typical VB features of Co metal, CoOx Co3O4, and a mixed phase between any two adjacent features were observed and well corroborated with core level changes. Very significant and characteristic changes were observed with Co 3d features in the VB for each stage from Co oxidation to Co3O4 as well as Co3O4 reduction to CoOx Co(3O)4 and CoO can be reversibly obtained by alternating the conditions between 0.1 mbar of H-2 at 650 K and 0.1 mbar of O 2 at 400 K, respectively. A meaningful correlation is observed between the changes in work function with cation oxidation state; small changes in the stoichiometry can strongly influence the shift in Fermi level and changes in work function under NAP conditions. Reversible work function changes are observed at a constant BE (similar to 5 ev) between oxidation and reduction conditions. While the O 2 p derived feature for CoOx was observed at throughout the redox conditions, the Co 3d band and molecular oxygen or hydrogen vibration feature shifts significantly underscoring the physicochemical changes, such as charge transfer energy and hence changes in satellite intensity. The peak close to E-F originated from the 3d(6)L final state of the octahedral Co3+ 3d band of Co3O4.